Cyclic dinucleotides modulate induced type I IFN responses in innate immune cells by degradation of STING. Issue 7 (10th April 2017) - Rueckert, Christine; Rand, Ulfert; Roy, Urmi; Kasmapour, Bahram; Strowig, Till; Guzmán, Carlos A.
ABSTRACT: The cyclic dinucleotides, GMP–AMP (cGAMP) and c‐di‐AMP [ bis ‐(3', 5')‐cyclic dimeric AMP], are potent type I IFN inducers via STING‐TBK1‐IRF3 cascade. They are promising adjuvants that promote antigen‐specific humoral and cellular immune responses in different preclinical models; however, an optimal outcome of vaccination depends on a balanced immune activation. Here, we characterize the process of IFN‐α induction by c‐di‐AMP and cGAMP in an in vitro model on the basis of primary mouse dendritic cells. Results obtained show decreased IFN‐α production upon prolonged cell stimulation. We demonstrate that this effect depends on c‐di‐AMP/cGAMP‐mediated down‐regulation of stimulator of IFN gene (STING) protein levels. These results were confirmed by using human peripheral blood mononuclear cell–derived dendritic cells. Studies performed to explore the potential mechanism of STING modulation suggested proteolytic degradation to be a contributing factor to the observed decrease in cellular STING levels. Our work contributes to the elucidation of the molecular mode of action of vaccine constituents, which, in turn, is a prerequisite for the rational design of vaccines with predictable efficacy and safety profiles—Rueckert, C., Rand, U., Roy, U., Kasmapour, B., Strowig, T., Guzmán, C. A. Cyclic dinucleotides modulate induced type I IFN responses in innate immune cells by degradation of STING. FASEB J. 31, 3107–3115 (2017). www.fasebj.org